How Multimedia Support Collaborative Research: Best Practices - Cristóbal Ballesteros Regaña; Rocío P. Piñero-Virué; Miguel Mª Reyes-Rebollo (Research in Social Sciences and Technology- OpenED Network, 2019)
The purpose of this article is to evaluate the potential for online multimedia materials as alternative learning tools for the collaborative training of teachers in the design of research-based teaching. A case study using a team of three trainee teachers was used to develop a process of initial training in the design of a constructivist and research-based teaching unit supported by online multimedia material. The results obtained from the research allowed some principles to be identified and basic recommendations and alternative lines of action to be given for designing online multimedia materials. Online multimedia materials can be alternative teaching tools that contribute, with other materials, to the development of constructivist, collaborative, and research-based strategies which help provide the necessary support for improving the initial and ongoing training of new teachers in the design of teaching from a research perspective.